1979
DOI: 10.1113/jphysiol.1979.sp012622
|View full text |Cite
|
Sign up to set email alerts
|

The influence of corticosteroids on the secretion of corticotrophin and its hypothalamic releasing hormone

Abstract: SuMAY1. The effects of stress, adrenalectomy and corticosterone treatment on the functional activity of the hypothalamo-pituitary-adrenocortical system have been studied using highly sensitive and precise bio-assay methods for the determination of ACTH and CRH.2. Adrenalectomy resulted in a rise and corticosterone treatment a fall in the hypothalamic CRH content and the plasma ACTH concentration.3. Stress caused a fall followed by a rise in the hypothalamic CRH content, a rise in the pituitary and plasma ACTH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
38
1

Year Published

1980
1980
1993
1993

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 34 publications
3
38
1
Order By: Relevance
“…Furthermore, the attenuated corticotrophin-releasing activity of hypothalamic extracts from Brattleboro rats is restored by the addition of small (pg) quantities of AVP to the extract (24, 25) whilst systemic administration of desmopressin increases the circulating ACTH concentrations in these rats (26). Our observation that dexamethasone readily abolished the HPA response to stress in both Long Evans and Brattleboro rats is not surprising since, with the treatment regime employed, the steroid would be expected to block the secretion of both AVP and CRF-41 from the parvocellular neurons (14, 27, 28) and to exert effects at the pituitary level (29). The steroid-induced reductions in the basal pituitary-adrenocortical activity described here and elsewhere (30) may be explained similarly.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the attenuated corticotrophin-releasing activity of hypothalamic extracts from Brattleboro rats is restored by the addition of small (pg) quantities of AVP to the extract (24, 25) whilst systemic administration of desmopressin increases the circulating ACTH concentrations in these rats (26). Our observation that dexamethasone readily abolished the HPA response to stress in both Long Evans and Brattleboro rats is not surprising since, with the treatment regime employed, the steroid would be expected to block the secretion of both AVP and CRF-41 from the parvocellular neurons (14, 27, 28) and to exert effects at the pituitary level (29). The steroid-induced reductions in the basal pituitary-adrenocortical activity described here and elsewhere (30) may be explained similarly.…”
Section: Discussionmentioning
confidence: 99%
“…9 In addition, glucocorticoids produce relatively rapid reduction of corticotropin (adrenocorticotropic hormone, ACTH) release before demonstrable effects of corticotropin biosynthesis, 10,11 as well as rapid inhibition of basal or circadian release of corticotropin-releasing hormone (CRH) from hypothalamus and CRH-stimulated release of corticotropin from the pituitary. 8,12,13 This rapid inhibition is not affected by pretreatment with cycloheximide in a dose that inhibits protein synthesis. 14 This evidence relates well to our demonstrations in human subjects that, after intravenous administration of methylprednisolone, an initial rapid monoexponential decline of cortisol 5 and whole blood histamine occurs.…”
mentioning
confidence: 96%
“…At this time after adrenalectomy, hypothalamic CRH, and ACTH in pituitary and plasma, are elevated whilst plasma corticosterone is low (Buckingham & Hodges, 1974;Buckingham, 1979) but, in contrast to the decrease in hypothalamic enkephalin content, these changes persist.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown (Buckingham & Hodges, 1977;Buckingham, 1979) that hypothalamic CRH and pituitary ACTH are reduced by betamethasone but increased by ether stress. However, we found that both minor stress (handling and injection) and dexamethasone treatment increased hypothalamic enkephalin content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation